Eficiência energética em processo produtivo: caso de estudo em motores elétricos em uma linha de fabricação de bloco do motor diesel - Lima, Helder de (2013)
This monograph detaches a work of Energy Efficiency in the production line of the diesel engine block model MD13 in VOLVO Curitiba's factory, in the state of Paraná, Brazil. It was observed that the implementation of a simple solution, with reduced cost, will generate countless significant benefits for the VOLVO DO BRASIL plant in Curitiba, such as the reduction of the energy consumption and the prolongation of the equipments’ useful life on the diesel engine model MD13 production line. Important themes are approached, such as, theoretical concepts, efficiency sceneries, energy consumption, waste, economy and energy conservation, and still, costs and investments associated to the Energy Efficiency. In the world ranking Brazil is the 10 o (tenth) highest consumer of electric energy in the world and the highest consumer in South America. The concentration of the Energy Efficiency improvement in the residential and industrial sectors is some of the policies adopted by the Brazilian government, as well as the increase of the renewable energies.